If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + x = 59 Reorder the terms: 5 + 2x + x = 59 Combine like terms: 2x + x = 3x 5 + 3x = 59 Solving 5 + 3x = 59 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 59 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 59 + -5 3x = 59 + -5 Combine like terms: 59 + -5 = 54 3x = 54 Divide each side by '3'. x = 18 Simplifying x = 18
| -(x+9)= | | 5x=28+3x | | 6x+2y-3x+7y= | | -2c(8c-7)(c+5)=0 | | X^2-y=0.75 | | y=(4x-1)ln(5x-1) | | [6/2]-[3x0]= | | -6(x+2)=9x-3 | | p^6-52p^4+640p^2-1024=0 | | 3(1-2x)+7= | | Y=-3x+180 | | 2p+3q+5r+7= | | -0.5x+0y=14 | | -7t+11=-73 | | (v^2-9v+18)(3v+27)=0 | | -18=8x-9x-5x | | w^2-w-18=0 | | 0=10t^2+25t-30 | | Ln(x+1)=0.43 | | 30x+20y=248 | | y+5x+13= | | ((ln)x)=10 | | ln(1-4k)=8k | | xy+x+y=23 | | tan(2x)=cos(x) | | -2[5-(5-4s)]+4=-3s | | 3x+4-2=9.5 | | 10-p=4p-12 | | 5(ln(x)/ln(7))-(ln(49x)/ln(7))=-2 | | -9(2+A)+4(2A+9)=1 | | 21x+3y-48=0 | | (7-2i)/(3-4i) |